Dimensi Dakwah dalam Tradisi Sedekah Bumi - siti Humaningsih (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2021)
ABSTRACTThe research method uses qualitative while the theory used is acculturation theory which explains cultural adjustment with a renewal, namely the meaning of Islam contained therein. The study results indicate that this research includes the dimensions of da'wah in the earth alms tradition. The categories of da'i in this tradition are village officials, religious leaders, traditional stakeholders, and puppeteers. The message of da'wah in this tradition is wayang stories, songs, or puppet chants that contain prayers and prayers that are read during the baritan convention. The media of da'wah is through fasting, wayang kulit performances, tahlilan, baritan and food gathering. Positive values arise for the community, such as the value of alms, gratitude, da'wah, aqidah, and ahlak. The impact of this research is expected to be a reference source for traditional da'wah models in Indonesia or analysis related to traditional da'wah.Keywords: Tradition; Sedekah Bumi; Elements of Da'wah